EXPRESSION OF ALLEGORICAL MEANING IN LITERARY TEXTS - Jurayev Nabi Narziyevich (Western European Studies, 2025)
This article discusses the expression of allegorical and figurative meanings in literary texts, as well as their artistic techniques and linguistic features. It analyzes the semiotic characteristics of allegory, the relationship between allegory and symbol, allegory and metaphor, the discursive peculiarities of allegorical texts, and the distinctive features of everyday, literary, and religious allegorical texts. The study also addresses genre-specific traits of allegorical works and the expression of allegorical meaning in fairy tales and fables, providing reflections on research and findings in these areas.
Keywords: linguistics; literary studies; literary text; allegory